The Effect of Principal Leadership on Teacher Performance through Work Motivation as an Intervening Variable at Private Vocational Schools in Medan Tuntungan District - Nirmawati Nirmawati; Sri Nurabdiah Pratiwi; Irvan Irvan (Indonesian Journal of Education and Mathematical Science, 2023)
This study aims to analyze the role of leadership in schools on teacher performance, and the role of teacher motivation as mediating the role of leadership in schools on teacher performance. The population of all Vocational High School teachers in the Medan Tuntugan District was 112 teachers. The sample was determined using a proportional random sampling technique, so that the total sample for the study was 88 teachers. The data collection tool used was a questionnaire measured by a 5-point Likert scale, while the data analysis technique used Path Analysis. Based on the results of the study, it shows that the principal's leadership has fostered good cooperation and relationships, effectiveness, participation, delegating time, and delegating authority. The teachers studied had the motivation to excel, the need to expand association, the need to master a job. Teachers also have good performance as indicated by the fulfillment of work quality, work quantity, reliability and attitude. The findings of this study also show that the stronger the principal's leadership will improve teacher performance, the principal's leadership is also able to increase teacher work motivation, and work motivation will contribute to teacher performance.